Characteristics of Microseismic Waveforms Induced by Underground Destress Blasting: Comparison With Those Induced by Ground Blasting and Coal Mining - Kan, Jiliang; Dou, Linming; Li, Jiazhuo; Li, Xuwei; Bai, Jinzheng; Wang, Mengqi (Frontiers in Earth Science, 2022)
Some industrial activities in mines, such as underground coal mining, destress blasting for preventing rockburst and ground blasting for mining, can cause microseismic occurrence. The microseismic waveform contains abundant information on hypocenter and propagation path, which are valuable to study the microseismic mechanism and propagation. Therefore, this paper adopts the multifractal detrended fluctuation analysis (MF-DFA) and the Hilbert-Huang transform (HHT) method to study the nonlinear and time-frequency-energy characteristics of different types of microseismic waveforms. The microseismic waveform induced by mining and destress blasting has a higher dominant frequency (above 100 Hz) and shorter duration (less than 0.5 s) than ground blasting-induced microseismic waveform (dominant frequency below 25 Hz and duration more than 3 s). Further, for destress blasting-induced microseismic, the waveform is characterized by rich spectrum, complex energy attenuation, developed coda wave and clear multifractal characteristics, which indicate that the waveform is more complex and variable. The complex underground geological environment and the superposition effect of blasting stress and mining stress are the main reasons. Moreover, the propagation distance and source energy of microseismic also greatly affect waveform characteristics. The results show that the waveform information of destress blasting-induced microseismic can describe the release process of blasting stress and mining stress. Based on this, a blasting efficiency index Be was proposed to evaluate the effect of pressure relief and the classification system was developed. Then, the evaluate index was successfully applied to 63 rounds of destress blasting in the Yutian Coal Mine. The research results can provide a certain reference for some work such as the identification of different microseismic, rock dynamic failure process analysis, and evaluation of destress blasting effect.